ZnO–ZnCr2O4 composite prepared by a glycine nitrate process method and applied for hydrogen production by steam reforming of methanol. Issue 34 (10th August 2022) - Yu, Chung-Lun; Sakthinathan, Subramanian; Lai, Guan-Ting; Lin, Chia-Cheng; Chiu, Te-Wei; Liu, Ming-Che
Abstract : ZnO–ZnCr2 O4 composite for hydrogen production by steam reforming of methanol. Abstract : To address climate change, the energy crisis, and global warming, hydrogen (H2 ) can be used as a potential energy carrier because it is clean, non-toxic and efficient. Today, the mainstream industrial method of H2 generation is steam reforming of methanol (SRM). In this process, a zinc-based commercial catalyst is usually used. In this work, a ZnO–ZnCr2 O4 catalyst was successfully synthesised by the glycine nitrate process (GNP) and developed for use in H2 production by SRM. The specific surface area, porous structure and reaction sites of the zinc-based catalyst were effectively increased by the preparation method. The as-combusted ZnO–ZnCr2 O4 composite catalyst had a highly porous structure due to the gas released during the GNP reaction process. Moreover, according to the ZnO distribution and different G/N ratios, the specific surface area ( S BET ) of the as-combusted ZnO–ZnCr2 O4 catalyst varied from 29 m 2 g −1 to 46 m 2 g −1 . The ZnO–ZnCr2 O4 composite catalyst (G/N 1.7) exhibited the highest hydrogen production, 4814 ml STP min −1 g-cat −1, at a reaction temperature of 450 °C without activation treatment. After activation, the ZnO–ZnCr2 O4 composite catalyst achieved hydrogen production of 6299 ml STP min −1 g-cat −1 at a reaction temperature of 500 °C. The hydrogen production performance of the ZnO–ZnCr2 O4 composite powder was improved by the uniform addition of ZnO to ZnCr2 O4 . Based on the performance, this ZnO–ZnCr2 O4 composite catalyst has great potential to have industrial and economic impact due to its high efficiency in hydrogen production.